PENGGUNAAN RESPONSE SURFACE METHODOLOGY UNTUK OPTIMASI PROSES DEKAFEINASI MENGGUNAKAN KITOSAN DARI KULIT UDANG [The Use of Response Surface Methodology in Decaffeination Process with Chitosan] - Umar Santoso; Novia Tabahana; Henny Krissetiana H; Suhardi , (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
The objective of the present study was to determine the optimum condition of decaffeination process with chitosan in a model system using Response Surface Methodology. A 1000ppm caffeine solution was mixed with chitosan in varried concentrations, temperatures and process times. After filtration, caffeine in the filtrate was determined. The lower caffeine in the filtrate the more effective the decaffeination process. Result of the experiment showed that among chitosan concentrations of 50, 60, 70, 80, 90, and 100 mg per 100 ml caffeine solution, the concentration of 70mg was the most effective. Among temperatures applied of 28, 40, 60, 80, 90, and 100oC, the most effective was of 90oC. And among the process times of 15, 30, 60, and 90 minutes, 15 minutes was the most effective. Result of optimatization using RSM showed that the optimum condition of decaffeination process were concentration of chitosan of 69,52mg, temperature of 89,71oC, and process time of 14,88 minutes. Under this condition the process diminished 79,56% of caffeine from the model system.